Color codes : modern theories of color in philosophy, painting and architecture, literature, music, and psychology - Riley, Charles A.; University Press of New England (Hanover : University Press of New England, 1995)
Color is an endlessly fascinating and controversial topic. "The first thing to realize about the study of color in our time is its uncanny ability to evade all attempts to systematically codify it," writes Charles A. Riley in this series of interconnected essays on the uses and meanings of color. Color Codes draws heavily on interviews with many of today's leading artists - Roy Lichtenstein, Frank Stella, Peter Halley, Lukas Foss, A. S. Byatt, and others - as well as seminal texts by a wide range of thinkers including Wittgenstein, Derrida, Barthes, Schoenberg, Kandinsky, Albers, Joyce, Pynchon, and Jung. Although Riley finds remarkable parallels among the theories and techniques of various disciplines, his emphasis is on the individual nature of the color sense. This resistance to a unified color theory gives the current aesthetic debate tremendous energy. "Because it is largely an unknown force, color remains one of the most vital sources of new styles and ideas, ready to be tapped by creative minds in the coming decades." In the studios of artists and composers, and in the recent writings of philosophers, psychologists, poets, and novelists, evidence of this emerging power is abundant. Creators, critics, and lay readers will find Color Codes accessible and stimulating.
Messiaen Slawson --Color in psychology. Kohler Arnheim Freud Jung Contemporary issues in color psychology Oliver Sachs.
Includes bibliographical references (pages [339]-342) and index.
Keywords: Color in art; Arts; Color (Philosophy); Color -- Psychological aspects